Bridging the pain gap after cancer surgery – Evaluating the feasibility of transitional pain service to prevent persistent postsurgical pain – A systematic review and meta-analysis - Raghu S. Thota; S Ramkiran; Aveek Jayant; Koilada Shiv Kumar; Anjana Wajekar; Sadasivan Iyer; M Ashwini (Indian Journal of Anaesthesia)
Background and Aims: The lack of a dedicated pain service catering to the postsurgical period has resulted in the origination of the pain–period gap. This has led to a resurgence of transitional pain service (TPS). Our objective was to evaluate the feasibility of TPS in pain practice among postsurgical cancer patients and its prevention of persistent postsurgical pain (PPSP), culminating in chronic pain catastrophising. Methods: The protocol for this meta-analysis was registered in the International Prospective Register of Systematic Reviews (ID: CRD42023407190). This systematic review included articles involving all adult cancer patients undergoing cancer-related surgery experiencing pain, involving pharmacological, non-pharmacological and interventional pain modalities after an initial systematic pain assessment by pain care providers across diverse clinical specialities, targeting multimodal integrative pain management. Meta-analysis with meta-regression was conducted to analyse the feasibility of TPS with individual subgroup analysis and its relation to pain-related patient outcomes. Results: Three hundred seventy-four articles were evaluated, of which 14 manuscripts were included in the meta-analysis. The lack of randomised controlled trials evaluating the efficacy of TPS in preventing PPSP and pain catastrophising led to the analysis of its feasibility by meta-regression. The estimate among study variances τ2 was determined and carried out along with multivariate subgroup analysis. A regression coefficient was attained to establish the correlation between the feasibility of TPS and its patient outcome measures and opioid-sparing. Conclusion: TPS interventions carried out by multidisciplinary teams incorporating bio-physical-psychological pain interventions have resulted in its successful implementation with improved pain-related patient outcomes mitigating the occurrence of PPSP.